To substitute is to replace a variable or expression with another variable or expression that may be equal to the original variable or expression. For example, start with the equation y = x + 4. Substitute -3 for x. This gives y = -3 + 4. Now simplify the equation, giving y = 1. One can the conclude that when x = -3, y = 1 and that (-3, 1) is a solution to the original equation y = x + 4.
# | A | B | C | D |
E | F | G | H | I |
J | K | L | M | N |
O | P | Q | R | S |
T | U | V | W | X |
Y | Z |
All Math Words Encyclopedia is a service of
Life is a Story Problem LLC.
Copyright © 2018 Life is a Story Problem LLC. All rights reserved.
This work is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License